17.7k views
0 votes
Todd has created the following diagram to prove the Pythagorean theorem. He drew (triangle)ABC with leg lengths a and b and hypotenuse length c. Then he drew altitude CZ to the hypotenuse. He determines that c/a=a/z and c/b=b/y. Then he determines that cx=a^2 and cy=b^2. What is the next step in proving the theorem?

Todd has created the following diagram to prove the Pythagorean theorem. He drew (triangle-example-1
User Majak
by
4.8k points

2 Answers

1 vote

Answer: cx + cy = a² + b²

Explanation:

User Teja Kumar Bethina
by
5.5k points
6 votes

Answer:

cx + cy = a² + b²

Explanation:

Next step is adding up cx and cy:

  • cx + cy = a² + b²

Then followed by:

  • c(x+y) = a² + b²
  • c² = a² + b²
User LeSchwambo
by
5.3k points